Pesticide exposure and emergency response - Skoglund, L. G., author; McDonald, S. K., author; Colorado Environmental Pesticide Education Program, publisher (Colorado State University. Libraries, 2006)
This fact sheet defines pesticide exposure and explains first aid for pesticide poisonings.
CEPEP 5/00, updated 6/06.
PLEASE NOTE: This fact sheet is a historical document and some information may not reflect current federal and state laws and regulations and best practices.
Keywords: Pesticides -- Accidents; Pesticides -- Toxicology; Accidental poisoning; First aid in illness and injury